The impact of enterprises’ scientific capabilities on innovation performance: evidence from an empirical analysis and simulation model - Weijie Zhu; Wucheng Han; Ruoyu Lu; Jiasu Lei (Humanities & Social Sciences Communications)
Abstract As the interaction between science and technology intensifies, the role of science in driving technological innovation has become increasingly significant. Enterprises, as key actors in market competition and innovation, can gain a substantial competitive advantage and contribute to industrial transformation by engaging in basic research. This study focuses on science-based enterprises, defining enterprises’ scientific capabilities in two dimensions: internal scientific capabilities and external scientific capabilities. Through a combination of empirical and simulation research, this study examines the mechanisms by which scientific capabilities influence innovation performance. The results demonstrate that internal scientific capabilities significantly enhance enterprise innovation, underlining the importance of engaging in basic research to foster scientific innovation performance. External scientific capabilities, particularly in terms of quantity, also contribute positively to innovation performance, emphasizing the value of industry-university-research collaborations and the effective absorption of scientific knowledge. Furthermore, scientific innovation intensity mediates the relationship between scientific capabilities and innovation performance, with science-based innovation acting as a bridge between scientific discoveries and technological advancement. While scientific research funding moderates the impact of internal scientific capabilities on innovation performance, it shows no significant moderating effect on external scientific capabilities. Based on these findings, the study proposes four pathways for enterprises to enhance innovation performance: independent innovation, collaborative R&D, scientific knowledge absorption, and technical iteration. This research advances both enterprise capability theory and technological innovation theory by addressing the gap in understanding how enterprises’ scientific capabilities influence innovation and providing actionable insights for the development of science-based enterprises.